Impacts of a high-discharge submarine sewage outfall on water quality in the coastal zone of Salvador (Bahia, Brazil). Issue 1 (15th May 2016) - Roth, F.; Lessa, G.C.; Wild, C.; Kikuchi, R.K.P.; Naumann, M.S.
Abstract: Carbon and nitrogen stable isotopic signatures of suspended particulate organic matter and seawater biological oxygen demand (BOD) were measured along a coastal transect during summer 2015 to investigate pollution impacts of a high-discharge submarine sewage outfall close to Salvador, Brazil. Impacts of untreated sewage discharge were evident at the outfall site by depleted δ 13 Corg and δ 15 N signatures and 4-fold increased BOD rates. Pollution effects of a sewage plume were detectable for more than 6 km downstream from the outfall site, as seasonal wind- and tide-driven shelf hydrodynamics facilitated its advective transport into near-shore waters. There, sewage pollution was detectable at recreational beaches by depleted stable isotope signatures and elevated BOD rates at high tides, suggesting high bacterial activity and increased infection risk by human pathogens. These findings indicate the urgent necessity for appropriate wastewater treatment in Salvador to achieve acceptable standards for released effluents and coastal zone water quality. Highlights: Pollution by untreated sewage discharge is evident at the outfall and in Salvador's coastal zone. Seasonal wind- and tide-driven surface currents control advective transport of discharged sewage. Water quality at Salvador's recreational beaches is impacted by a plume of untreated sewage.